Discursos sobre a surdez do sujeito patológico ao sujeito de cultura: um paradoxo da inclusão? - Silveira, Tatiane De Lima [UNIFESP] (2020)
This thesis aims to reflect about the following question: what is the subject-position of the deaf child in the speech of teachers of Bilingual Education Schools for the Deaf Children and Regular Schools? To answer this question, a semi-structured interview was conducted with focus on spontaneously spoken words that, according to teachers, are directly related to the word deafness. The vernaculars were tabulated, and the interview recorded and transcribed. Discourse analysis was performed using an interpretation method of configuration signifiers and discursive chains related to deafness, based on their socio-historical context. The research was carried out with 10 teachers from a Municipal School of Bilingual Education (EMEBS) and another 10 teachers from 3 Municipal Schools (in a Center for Early Childhood Education, a Municipal School of Early Childhood Education and a Municipal Elementary School), all from Sao Paulo City. Thus, this study contributes to understand how deaf people are seen and how they are included at school environment. There were speeches with multifaceted views about deaf people. Such representations pass through the following deaf subject-position: pathological, bilingual and cultural; showing that these discourses are linked to historical conceptions about what would be the best methodology to educate the deaf: oralism, bilingualism and what will be called “culturalism” here. Throughout the analysis, it was possible to notice that while deaf people are included, they are excluded and when they are excluded, they can see themselves included. That is the inclusion paradox.